Modeling Response of Concrete Material due to Biaxial Loading using Finite Element Method Software Based - Data Iranata; Endah Wahyuni; Aniendhita Rizki Amalia; Sylvya Anggraini (IPTEK The Journal of Engineering, 2015)
Generally the concrete behavior can be observed by the experimental analysis. However, since the computer technology development has been increased rapidly, the computer simulations are also able to represent the detail behavior of concrete. This paper presents the modeling response of concrete material subjected to biaxial loading using finite element method software based. The plain concrete plates with dimensions 200mm x 200mm x 50mm and 150mm x 150mm x 50mm are analyzed using various combinations of biaxial loading. The results of the biaxial load combinations are covering the three non-linear regions of compression–compression, compression–tension, and tension–tension. The results of finite element analysis are also show good agreement to the experimental results that been taken from the previous study. The comparison results the difference between analytical and experimental study are less than 5%. Therefore, the concrete material model based on this finite element method software can be used to simulate the responses in the real condition.